(3JaSjQ GdbQBfs - (3YHO Gddg Hf YHGS Hf YHO GdeWdH GdbQTj GdgGTej , CHh GdYHGS , J (B68 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje MOKJ GHhYdi Hf GdMSf Hf eMeO Hf LYaQ bGd MOKfG YHOGddg s
(3BNQgG (B:s
(3fRdJ gPGf GdShQJGf dHjO Hf YGUe GdjghOi GdPi SMQ ddfHi Ydjg GdSdGe abQ GdfHi Ydjg GdSdGe Ydi SMQ aaQL Gddg Yfg Pdc hGdMeO Qddg QH GdYGdejf Je HMeO Gddg s
(3GdfSNI HgG MhGTs
(3HgG JedjcGJs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs